PENGUNGKAPAN MANAJEMEN RISIKO DITINJAU DARI UKURAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, PROFITABILITAS DAN LEVERAGE (Studi pada Perusahaan Manufaktur yang Tercatat di BEI Tahun 2016-2018) - Mohammad Hendro Leksmono (JURNAL ILMIAH EDUNOMIKA, 2020)
Research purposes were determined the effect of company size, management ownership, profitability, and leverage on risk management disclosures in manufacturing companies listed on the Indonesian Stock Exchange in 2016-2018. The research type is a quantitative descriptive. The research population is manufacturing companies listed on the Indonesian Stock Exchange in 2016-2018. Determination of the sample used purposive sampling technique. The data collection method used the documentation method. The data analysis technique used statistical analysis, namely multiple linear test, F test, and t test. The results how that 1) company size has a positive and significant effect on the risk management disclosure of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018; 2) managerial ownership has no significant effect on the risk management disclosure of manufacturing companies listed on the Indonesia Stock Exchange 2016-2018; 3) profitability has no significant effect on the risk management disclosure of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018; 4) Laverage has a significant effect on the risk management disclosure of manufacturing companies listed on the Indonesia Stock Exchange 2016-2018; and 5) Company size, managerial ownership, profitability, and leverage simultaneously have a significant effect on the risk management disclosure of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Keywords: company size, managerial ownership, profitability, leverage, risk management disclosure.